An extension of the stochastic two-scale convergence method and application - Heida, Martin (Asymptotic analysis, 2011)
The stochastic two-scale convergence method, recently developed in an article by Zhikov and Piatnitskii [Izv. Math. 70(1) (2006), 19-67] is extended to arbitrary probability spaces and is now based on the theory of stochastic geometry instead of rand